Envisioning enabling environments for young women with perinatal infections of Human Immunodeficiency Virus in Africa : a participatory creative new-materialist approach. - Hendricks, Lynn Avril (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.